The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/ajsp.12388
|View full text |Cite
|
Sign up to set email alerts
|

Negative expectations and bad relationships: Effects of negative metastereotypes on doctor–patient relationships

Abstract: This research aimed to examine the effects of negative metastereotypes (i.e., patients believe that doctors have negative opinions about them) and conflict experience on doctor-patient relationships. A 2 9 2 experimental study was conducted on 84 outpatients who were randomly assigned to either a negative metastereotype activation (NMSA) condition or a nonnegative metastereotype activation (non-NMSA) condition. Each group consisted of patients with and without conflict experience (CE). Intergroup anxiety and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 28 publications
2
9
0
Order By: Relevance
“…Another study conducted by He et al (2019) revealed that negative metastereotypes result in worsening the relationship between doctor and patient. It showed that how the doctor-patient relationship is directly influenced by metastereotypes affecting individuals' expectations, personal judgment, and contact experiences.…”
Section: Metastereotypes and Supervisor-supervisee Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study conducted by He et al (2019) revealed that negative metastereotypes result in worsening the relationship between doctor and patient. It showed that how the doctor-patient relationship is directly influenced by metastereotypes affecting individuals' expectations, personal judgment, and contact experiences.…”
Section: Metastereotypes and Supervisor-supervisee Relationshipsmentioning
confidence: 99%
“…Different instructions were provided to the positive metastereotype group, negative metastereotype group, and control group for the induction of the appropriate metastereotypes through Metastereotype Activation Task (He at al., 2019). The instruction given to the positive metastereotype group was: "how many positive impressions do you think your supervisor has about your lifestyle, academic ability, personality, and so on?…”
Section: Metastereotype Activation Taskmentioning
confidence: 99%
“…Scholars at home and abroad have also conducted in-depth discussions on the path and countermeasures of doctor–patient disputes. For example, Chen Zheng and Peng Hua proposed that hospitals should make full use of the information system’s key monitoring role in medical safety indicators and establish a risk sentinel early warning mechanism to deal with potential disputes [ 13 ]; Gerds and Lerner pointed out that artificial intelligence should be used to reduce medical risks The advantages of prediction and management are to quantify medical risk early warning indicators and establish a risk early warning system. Hospitals should closely prevent and control potential risk factors with higher risk levels to make effective interventions as soon as possible when doctor–patient disputes occur [ 14 , 15 ]; Rubin believes that hospitals should focus on the quality of medical care, play an active role in the risk management of evidence-based medicine in the process of diagnosis and treatment, and curb the emergence of doctor–patient conflicts from the source [ 16 ]; while Zhang, Hu, Tao, etc.…”
Section: Introductionmentioning
confidence: 99%
“…8 , 9 Stigma can increase patients’ inter-group anxiety and destruct physician-patient relationships, which is especially obvious among the people who once had conflicts with physicians. 10 …”
mentioning
confidence: 99%
“…8,9 Stigma can increase patients' inter-group anxiety and destruct physician-patient relationships, which is especially obvious among the people who once had conflicts with physicians. 10 Devoid of scientific research instruments, previous studies generally focused on a specific theme of physicians' occupational stigma through qualitative analysis. For instance, Riley et al found that physicians had a relatively high stigma toward mental illness, work-related stress, and burnout, showing the intolerance of their vulnerability, so that they would continue their work although they feel uncomfortable.…”
mentioning
confidence: 99%